Metropolitan Land Values - Albouy, David; Ehrlich, Gabriel; Shin, Minchul (The Review of Economics and Statistics, 2018)
We estimate the first cross-sectional index of transaction-based land values for every U.S. metropolitan area. The index accounts for geographic selection and incorporates novel shrinkage methods using a prior belief based on urban economic theory. Land values at the city center increase with city size, as do land-value gradients; both are highly variable across cities. Urban land values are estimated at more than two times GDP in 2006. These estimates are higher and less volatile than estimates from residual (total - structure) methods. Five urban agglomerations account for 48% of all urban land value in the United States.